2022
DOI: 10.1186/s13018-022-03059-8
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0001174 facilitates osteosarcoma cell proliferation, migration, and invasion by targeting the miR-186-5p/MACC1 axis

Abstract: Background Studies of aberrantly expressed circular RNAs (circRNAs) can provide insights into the molecular mechanisms of osteosarcoma (OS). However, the role of circ_0001174 in OS progression remains unknown. This study is aimed to identify differentially expressed circRNAs and messenger RNAs (mRNAs) in patients with OS and to investigate potential regulatory ways of circ_0001174. Methods High-throughput sequencing was performed to screen aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…30 Circ_0001174 was highly expression and promoted OS progression. 31 Circ-LRP6, has been shown to serve as an oncogene in different cancers, but its mechanism of action in OS is not completely comprehended. In this study, circ-LRP6 was found to be overexpressed in osteosarcoma tissues and cell lines, and that silencing circ-LRP6 inhibited proliferation, migration, and invasion of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Circ_0001174 was highly expression and promoted OS progression. 31 Circ-LRP6, has been shown to serve as an oncogene in different cancers, but its mechanism of action in OS is not completely comprehended. In this study, circ-LRP6 was found to be overexpressed in osteosarcoma tissues and cell lines, and that silencing circ-LRP6 inhibited proliferation, migration, and invasion of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circ_LARP4 presented down‐regulation in non‐small cell lung cancer (NSCLC) cell lines, and overexpression of it can hinder the proliferation and migration of NSCLC cells and stimulate cell apoptosis 30 . Circ_0001174 was highly expression and promoted OS progression 31 . Circ‐LRP6, has been shown to serve as an oncogene in different cancers, but its mechanism of action in OS is not completely comprehended.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA NEAT1 sponges miR‐186‐5p and promotes the progression of osteosarcoma invasion and EMT ( 16 ). Via miR-186-5p, circ_0001174 promotes osteosarcoma progression ( 17 ). Our results showed that circ0038632 could regulate the expression of miR-186 by sponging it ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%